The Mitotic Exit Network Regulates Spindle Pole Body Selection During Sporulation of Saccharomyces cerevisiae. Issue 2 (1st June 2017) - Renicke, Christian; Allmann, Ann-Katrin; Lutz, Anne Pia; Heimerl, Thomas; Taxis, Christof
Abstract: Age-based inheritance of centrosomes in eukaryotic cells is associated with faithful chromosome distribution in asymmetric cell divisions. During Saccharomyces cerevisiae ascospore formation, such an inheritance mechanism targets the yeast centrosome equivalents, the spindle pole bodies (SPBs) at meiosis II onset. Decreased nutrient availability causes initiation of spore formation at only the younger SPBs and their associated genomes. This mechanism ensures encapsulation of nonsister genomes, which preserves genetic diversity and provides a fitness advantage at the population level. Here, by usage of an enhanced system for sporulation-induced protein depletion, we demonstrate that the core mitotic exit network (MEN) is involved in age-based SPB selection. Moreover, efficient genome inheritance requires Dbf2 /20 -Mob1 during a late step in spore maturation. We provide evidence that the meiotic functions of the MEN are more complex than previously thought. In contrast to mitosis, completion of the meiotic divisions does not strictly rely on the MEN whereas its activity is required at different time points during spore development. This is reminiscent of vegetative MEN functions in spindle polarity establishment, mitotic exit, and cytokinesis. In summary, our investigation contributes to the understanding of age-based SPB inheritance during sporulation of S. cerevisiae and provides general insights on network plasticity in the context of a specialized developmental program. Moreover, the improved system for a developmental-specific tool to induce protein depletion will be useful in other biological contexts.